Livelihood and vulnerability in the wake of Typhoon Yolanda: lessons of community and resilience - Eadie, Pauline; Atienza, Maria Ela; Tan-Mullins, May (Springer, 2020)
Livelihood strategies that are crafted in ‘extra-ordinary’ post-disaster conditions should also be able to function once some semblance of normalcy has resumed. This article aims to show that the vulnerability experienced in relation to Typhoon Yolanda was, and continues to be, directly linked to inadequate livelihood assets and opportunities. We examine the extent to which various livelihood strategies lessened vulnerability post-Typhoon Yolanda and argue that creating conditions under which disaster survivors have the freedom to pursue sustainable livelihood is essential in order to foster resilience and reduce vulnerability against future disasters. We offer suggestions to improve future relief efforts, including suggestions made by the survivors themselves. We caution against rehabilitation strategies that knowingly or unknowingly, resurrect pre-disaster vulnerability. Strategies that foster dependency, fail to appreciate local political or ecological conditions or undermine cooperation and cohesion in already vulnerable communities will be bound to fail. Some of the livelihood strategies that we observed post-Typhoon Yolanda failed on some or all of these points. It is important for future policy that these failings are addressed.